Development of reduced fat cream cheese by using inulin and WPC as a fat replacer - N, Krishna K; Ghosh, Bikash C (Indian Journal of Dairy Science, 2020)
Cream cheese is a soft, mild, rich, creamy white, slightly acidic, unripened cheese with diacetyl flavour. The focus of the present investigation was to develop reduced fat cream cheese by using inulin and WPC as a fat replacer. Cream Cheese (control) and Reduced Fat Cream Cheese (RFCC) were prepared by fermentation of cream and skim milk separately followed by straining with muslin cloth and hanging for 12-13hours at 7-8â°C. Fermented mass and fermented cream was then mixed in 3:1 and 6:1 ratio to obtain control and RFCC, respectively. Inulin and WPC of 4 and 6% were incorporated in RFCC. Cheese made with 4% inulin scored significantly (p<0.05) higher body and texture and overall acceptability scores indicating the best resultant product. Â The moisture content and firmness showed inverse relationship whereas spreadability showed direct relationship with inulin incorporation. RFCC with 4% inulin showed better spreadability (0.0167g.sec), lowest firmness (1.73N) and moisture content (75.59%). Â Â Among 4 and 6%, incorporation of 4% WPC in RFCC, showed better sensory, physico chemical and textural properties than those made with 6% WPC. Moisture and firmness showed inverse relationship while spreadability and acidity increased significantly (p<0.05) with increase in WPC level. Cheese made with combination of 2% inulin and 2% WPC scored significantly (p< 0.05) lower score than control. The spreadability of 4% inulin incorporated cheese was significantly (p<0.05) higher followed by the cheese made combination of 2% inulin and 2% WPC than RFCC.Â Total solids and fat contents of experimental samples were significantly (p<0.05) lower than control cheese.Â Incorporation of 4% inulin in reduced fat cream cheesed was adjudged best among the incorporation of inulin, WPC and their combination.